2011
DOI: 10.1007/s12562-011-0403-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation and population structure of the Pacific cod Gadus macrocephalus in Korean waters revealed by mtDNA and msDNA markers

Abstract: To investigate the extent of genetic differentiation among wild populations of the Pacific cod Gadus macrocephalus, we have examined genetic polymorphism at five locations within Korean waters [Boryeong in the West Sea (WC-BR); Jinhae Bay in the South Sea (SC-JH); Jumunjin (EC-JM), Jukbyeon (EC-JB), and Bangeojin (EC-BJ) off the eastern coast of Korea] using mitochondrial DNA (mtDNA) control region and microsatellite DNA (msDNA) markers. Nucleotide sequence analysis of 584 bp in the variable portion of the 5 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 29 publications
3
15
3
Order By: Relevance
“…In the present study, the use of the mtDNA nd2 showed appreciably more haplotype and nucleotide diversities than the use of the partial sequence of the mitochondrial control region, which has shown remarkably low diversity and shallow population structure in G. macrocephalus (Saitoh, ; Liu et al ., ; Gwak & Nakayama, ). Because the genetic differentiation among marine populations is expected to be low, highly polymorphic loci such as microsatellite markers are more powerful for identifying local population differentiation, as observed in several studies (Cunningham et al ., ; Gwak & Nakayama, ; Spies, ). Consequently, the mtDNA nd2 and multiple microsatellite markers were considered appropriate markers for revealing the presence of differentiation among G. macrocephalus samples collected from waters around Japan.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In the present study, the use of the mtDNA nd2 showed appreciably more haplotype and nucleotide diversities than the use of the partial sequence of the mitochondrial control region, which has shown remarkably low diversity and shallow population structure in G. macrocephalus (Saitoh, ; Liu et al ., ; Gwak & Nakayama, ). Because the genetic differentiation among marine populations is expected to be low, highly polymorphic loci such as microsatellite markers are more powerful for identifying local population differentiation, as observed in several studies (Cunningham et al ., ; Gwak & Nakayama, ; Spies, ). Consequently, the mtDNA nd2 and multiple microsatellite markers were considered appropriate markers for revealing the presence of differentiation among G. macrocephalus samples collected from waters around Japan.…”
Section: Discussionmentioning
confidence: 98%
“…452 bp by Liu et al . () and 584 bp by Gwak & Nakayama (), detected very low diversity among the G. macrocephalus population across a wide range of regions. Canino et al .…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…(Cha and Jung, 2012). (Seo et al, 2007;Lee et al, 2005;Cha et al, 2007), (Kim et al, 2013), (Choi and Gwak, 2011) , Park and Gwak (2009), , Yoon et al (2012), Baeck et al (2007, Seo et al (2010), Gwak and Nakayama (2011) , .…”
Section: 서 론 (Gadus Microcephalus)mentioning
confidence: 99%
“…In the southern East/Japan Sea, there are at least two spawning stocks (Zhang 1984;Gwak & Nakayama 2011): Jinhae Bay stock in Korean Peninsula and western Honshu (Noto Peninsula) stocks in Japanese islands ( Figure 1A). In Korean waters, cod spawn weakly adhesive demersal eggs Seo et al 2007), and spawning occurs mainly over sand and mud bottom during December through February with the peak in January (Lee et al 2009).…”
Section: Introductionmentioning
confidence: 99%